MANAJEMEN PROGRAM KURSUS INTENSIF BAHASA ARAB: STUDI PADA METODE MUSTAQILLI - Roviin Roviin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This study is to analyze the management of Mustaqilli intensive Arabic language course program held in Jakarta and online. The interview, observation, and documentation are used to collect primary data, while data analysis is based on descriptive qualitative techniques with three processes namely data reduction, data display, and verification. This study figures out that Mustaqilli intensive Arabic course management program has been well implemented with the fulfillment of management functions, i.e. planning, organizing, actuating, and controlling, related to the components of Arabic intensive course program management. The Mustaqilli learning Arabic method focused on student’s active participation through the formulation of Arabic sentence patterns in terms of language skills. By using the book al-‘Arabiyah li ghairi al ‘Arab and Audhahu al Manahij, this program is initiated to reach the whole targeted skills of learning Arabic. Although some deficiencies of this program need to be refined, especially related to user and time management, the Mustaqilli Arabic intensive course method is a good program as a reference to the management of Arabic intensive courses in all levels.